Hubungan Antara Pendidikan, Peran Orang Tua, dan Keterpaparan Media Massa Dengan Pernikahan Dini di Kecamatan Selo Kabupaten Boyolali - As-Syakiri, Dian Rizka; , Yuli Kusumawati, SKM, M.Kes (Epid) (2017)
Early marriage has an impact on the health of young couples because it can affect the high maternal mortality rate. The purpose of this study is to analyze the relationship between education, the role of parents, and exposure to mass media with early marriage in the District Selo Boyolali Regency. This type of research is observational research with case control approach (case control). The population in the study were all teenagers who were married before the age of 20 years in Selo District Boyolali District in 2016 which amounted to 101 respondents. Selection of sample in case group counted 75 people and control counted 75 people done by using technique of Proportional Random Sampling. The statistical test used Chi Square test. The result showed that there was a correlation between respondent education with early marriage (p-value = 0,005; OR = 3,273; 95% CI= 1,478-7,245), relation between maternal education of respondent and early marriage P-value = 0,005; OR = 12,719; 95% CI = 1,598-101,226), there is correlation between education of respondent father and early marriage (p-value=0,020; OR= 6,273; 95% CI= 1,340-29,368) Between the roles of parents with early marriage (p-value =0,000; OR= 12,581; 95% CI= 5,808-27,251), And there is a relationship between mass media exposure and early marriage in District Selo Boyolali Regency (p-value = 0,000; OR = 4,616; 95% CI = 2,307-9,235).